2019
DOI: 10.1111/apa.15045
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases detected by screening after arrival to Denmark in internationally adopted children

Abstract: Aim:To show the prevalence of selected infectious diseases among internationally adopted children (IAC) in Denmark. Background:Each year approximately 200 IAC arrive in Denmark. These are at increased risk of infectious diseases rarely seen in Danish children. Studies from the 1990s showed that 60% of IAC had infectious diseases and that the majority of these were undetected without screening. Methods:The study is a prospective study of medical records from children seen in the adoption clinic at Copenhagen Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
6
5
1
Order By: Relevance
“…The prevalence of intestinal parasites among internationally adopted children on arrival in Finland was 15.6%, which is comparable to the prevalence in adopted children in earlier studies in the other countries [3,[9][10][11]48] but lower than the reported in some recent works [6,[12][13][14][15]. This difference may be attributed to the development of better stool screening technologies, such as DNA-based methods, or reporting biases.…”
Section: Plos Onesupporting
confidence: 58%
See 1 more Smart Citation
“…The prevalence of intestinal parasites among internationally adopted children on arrival in Finland was 15.6%, which is comparable to the prevalence in adopted children in earlier studies in the other countries [3,[9][10][11]48] but lower than the reported in some recent works [6,[12][13][14][15]. This difference may be attributed to the development of better stool screening technologies, such as DNA-based methods, or reporting biases.…”
Section: Plos Onesupporting
confidence: 58%
“…Although many psychological explanations exist for growth and developmental delays also more physiological explanations are plausible. Intestinal parasite infections are common on arrival among internationally adopted children, especially among adoptees from countries with poor living conditions and subpar sanitation [3,4,6,[9][10][11][12][13][14][15][16]. Intestinal parasites in children are associated with growth and developmental delays [17][18][19] as well as micronutrient deficiencies [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies reported the proportion of IAC with protective antibody titres against different VPDs. In particular, observed protection rates ranged between 35% and 93% for diphtheria, 35% and 97% for tetanus, 12% and 89% for hepatitis B [ 5 , 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. This variability may likely be attributed to the heterogeneity of the study populations, due to the differences both in the number of children included in the studies and in the countries of origin of the IAC enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in accordance with data reported in the literature. Previous studies described a discrepancy between documentation (recorded vaccination) and serology (negative antibody titres) in 2–30% of IAC for diphtheria, 5–39% of IAC for tetanus, and 6–55% for hepatitis B [ 5 , 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 24 , 28 ]. In particular, concerning hepatitis B vaccination, this discrepancy may be explained by the fact that time since the last dose of vaccine received is predictive of the level of anti-HBs titres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation